Discontinuous Galerkin spectral element method to compute reflection and transmission of electromagnetic waves - Mesa-Mazo, Mónica (2018)
Modeling wave reflection and transmission is important for a diversity of applications in physics and engineering. Examples can be found in acoustics and electromagnetism. Computational wave propagation requires high order accuracy both in space and time to get accurate phase and dissipation properties. In this paper we derive and evaluate a high order accurate method based on Discontinuous Galerkin Spectral Element Method (DGSEM) to compute reflection and transmission of electromagnetic waves traveling in two homogeneous and isotropic media, separated by a thin plane interfaz, with different physical properties of permittivity " and permeability . To discretize in Space we used DGSEM over a two dimensional Transverse Electric Maxwell Equations. We derived a Riemann solver to compute the numerical flux between the interfaces of two elements of the computational mesh and to add boundary conditions. To discretize in time we use a third order low storage Runge-Kutta of Williamson. Results when compared with the analytical solution, showed spectral convergence in space and third order convergence in time.